Gyrase inhibitors can increase gyrA expression and DNA supercoiling. - Franco, R J (1989)
Treatment of bacterial cells with inhibitors of gyrase at high concentration leads to relaxation of DNA supercoils, presumably through interference with the supercoiling activity of gyrase. Under certain conditions, however, the inhibitors can also increase supercoiling. In the case of coumermycin A1, this increase occurs at low drug concentrations. Oxolinic acid increases supercoiling in a partially resistant mutant. We found that increases in chromosomal DNA supercoiling, which were blocked by treatment with chloramphenicol, were accompanied by an increased expression rate of gyrA. This result is consistent with gyrase being responsible for the increase in supercoiling. In wild-type cells, increases in gyrA expression were transient, suggesting that when supercoiling reaches sufficiently high levels, gyrase expression declines. Oxolinic acid studies carried out with a delta topA strain showed that drug treatment also increased plasmid supercoiling. The levels of supercoiling and topoisomer heterogeneity were much higher when the plasmid contained one of several promoters fused to galK. Since oxolinic acid causes an increase in gyrA expression, it appears that gyrase levels may be important in transcription-mediated changes in supercoiling even when topoisomerase I is absent.